MSC-derived exosomes promote proliferation and inhibit apoptosis of chondrocytes via lncRNA-KLF3-AS1/miR-206/GIT1 axis in osteoarthritis. Issue 21 (17th November 2018) - Liu, Yubao; Lin, Lupan; Zou, Rui; Wen, Chuanyang; Wang, Zhen; Lin, Fuqing
ABSTRACT: Background : Exosomes secreted by human mesenchymal stem cells (hMSCs) have been shown to promote cartilage regeneration. This study aimed to explore whether exosomal lncRNA-KLF3-AS1 derived from hMSCs can promote chondrocyte proliferation via miR-206/GIT1 axis in osteoarthritis (OA). Methods : hMSCs and MSC-derived exosomes (MSC-exo) were prepared for morphological observation and identification by transmission electron microscopy (TEM) and flow cytometry. IL-1β-induced OA chondrocytes and collagenase-induced mouse OA model were established for the further experiments. Luciferase activity assay was performed to test whether miR-206 could bind to KLF3-AS1 or GIT1. Cell proliferation and apoptosis were evaluated by CCK-8 assay and flow cytometry, respectively. Results : MSC-Exos increased chondrogenic genes Col2a1 (type II collagen alpha 1) and aggrecan, decreased hondrocyte hypertrophy markers MMP-13 (matrix metalloproteinase-13) and Runx2 (runt-related transcription factor 2) in chondrocytes isolated from OA model mice. Furthermore, MSC-Exos attenuated IL-1β-induced chondrocyte proliferation inhibition and apoptosis induction. Moreover, MSC KLF3-AS1 -Exos (exosomes derived from KLF3-AS1-overexpressing-MSCs) ameliorated IL-1β-induced chondrocyte injury. Results also demonstrated that KLF3-AS1 acted as a competitive endogenous RNA (ceRNA) by sponging miR-206 to facilitate GIT1 expression. In addition, miR-206 overexpression and GIT1 knockdown reversed MSC KLF3-AS1 -Exos-mediated attenuation of chondrocyte injury. Conclusion : Exosomal KLF3-AS1 derived from MSCs involved in MSC-Exos-mediated chondrocyte proliferation induction and chondrocyte apoptosis inhibition via miR-206/GIT1 axis. Abbreviation : G-protein-coupled receptor kinase interacting protein-1 (GIT1)